THE SIGNIFICANCE OF TEACHING FOREIGN LANGUAGES ON COMMUNICATION APPROACH - Giyasova Dilafruz Xamzayevna; Shavkatova Hulkar Xasan qizi (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract: This article examines the significance of teaching foreign languages through the communicative approach in modern education. In contemporary language pedagogy, the communicative approach is considered one of the most effective and widely accepted methods because it emphasizes the practical use of language in real- life situations rather than the memorization of isolated grammar rules and vocabulary items. The problem addressed in this study lies in the need to develop learners’ communicative competence, fluency, and confidence in using a foreign language for meaningful interaction in academic, social, and professional contexts. The methodology of the research is based on a qualitative theoretical approach, including descriptive analysis, comparative interpretation, and review of methodological and pedagogical literature related to communicative language teaching. The study analyzes the theoretical foundations of the communicative approach, its main principles, classroom applications, and its role in developing listening, speaking, reading, and writing skills in an integrated way. The main findings of the research show that the communicative approach significantly improves learners’ ability to use a foreign language effectively in authentic situations. It encourages active participation, learner- centered instruction, interaction, collaboration, and real-life communication. The approach also supports the development of communicative competence, sociolinguistic awareness, strategic language use, and learner autonomy. In addition, it creates a more motivating and engaging classroom environment than traditional teacher-centered methods.